Generalized hyperbolic discounting, borrowing aversion, and debt holding - Shinsuke Ikeda; Myong-Il Kang (Osaka University, Institute of Social and Economic Research (ISER), 2011)
Analysis of an original, broad, internet-based survey reveals that debt holding is related to three aspects of time discounting: (i) present bias, measured by the degree of declining impatience in the generalized hyperbolic discount function; (ii) borrowing aversion, captured by a sign effect - discounting future losses at a lower rate than future gains; and (iii) impatience, measured by the overall discount rate. Present-biased respondents are classified as naïve if their answers reveal themto be time-inconsistent procrastinators, and classified as sophisticated otherwise. Naïve respondents with more steeply declining impatience are more likely to be debtors, and are likely to have larger amounts of debt, whereas sophisticates display only insignificant positive association between declining impatience and debt holding. Responses indicative of a sign effect are negatively associated with debt holding. The marginal effect on debt of such a sign effect is larger in magnitude than the effect of one standard deviation increases both in declining impatience and in impatience. Survey responses indicative of high or declining impatience are associated with high debt-to-income ratios, borrowing on credit cards, and the experiences of having borrowed unsecured consumer loans, of having engaged in debt-restructuring, or of having declared personal bankruptcy.
Keywords: D03; D12; D91; 330; debt; generalized hyperbolic discounting; sign effect; overborrowing; naïve; sophisticate; Konsumentenverhalten; Zeitpräferenz; Private Verschuldung; Risikoaversion; Konsumtheorie